Penyandian File Word Berdasarkan Algoritma Rivest Code 5 (RC5) - Prabowo, Widodo Arif; Harahap, Annisa Fitri; Ismadiah, Ridha (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2018)
Nowadays, important data in the form of word files have been widely used. But there are still few who apply security techniques to the important files. Files that are confidential or important, if they fall into the hands of others may be misused or manipulated for certain purposes. The existence of document security applications built on cryptographic algorithms is one solution to solve the above problems. Cryptographic techniques secure a data or important files by encoding the data into a cipher that is difficult to understand again by others. The RC5 algorithm is one of the cryptographic technique algorithms that can be used to encode text from word files based on the RC5 algorithm so that it can improve the expression of important and confidential word files.